Physical- chemical characterization of the cocoa pod husk as a possible use in the production of agglomerated boards - Díaz-Oviedo, Andrés Felipe; Ramón-Valencia, Bladimir Azdrúbal; Moreno-Contreras, Gonzalo Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This research was based in the study of the physicochemical properties of the cocoa shell, variety CCN 51. In this sense, tests were carried out on the residues to determine the lignocellulose components, together with thermo-gravimetric tests and scanning electron microscopy. The results of the chemical composition showed values in a higher proportion of lignin, followed by cellulose and hemicellulose. In the thermal analysis, an initial peak associated with evaporated moisture was presented, in addition to four fragmentation stages, which correspond to the primary components of the residue. In the microstructure, a porous surface was observed, with the presence of micro pores and cell walls. In general, it can be concluded that the analyzed cocoa shell residues are a viable alternative of raw material from renewable sources in the agricultural sector for the manufacture of agglomerated boards with industrial applications.